Accounting services quality: a systematic literature review and bibliometric analysis - Vitor Azzari; Emerson Wagner Mainardes; FÃ¡bio Moraes da Costa (Asian Journal of Accounting Research, 2020)
The purpose of this paper is to identify and analyze the literature related to accounting and auditing services quality.The authors performed a systematic literature review that considered 22 papers on the topic. The authors also applied a bibliometric analysis in order to identify the main characteristics of these studies to discuss and provide research opportunities in this field.The bibliometric results indicate that most papers were published in services and marketing journals. The accounting service quality theme has been rarely researched in accounting field. In addition, based on our review, it was possible to identify that most papers use quantitative methods, such as surveys. The papers' conclusions diverge from each other, demonstrating a still fragmented literature.Taken together, the paper shows how accounting services quality is relevant and emerging topic that demands future research about accounting professionals' skills, their activities and how their customers perceive quality in an environment of constant change.The analyses indicate that there are six broad areas for future research on this topic: successes and failures of accounting services providers; the role of â€œclient centricityâ€; digital accounting services; services quality and accounting education; services quality when considering different types of accounting and auditing services and development of a measurement scale and a theoretical model for accounting services quality. This paper contributes for the ongoing debate about how competition, technology and innovation are changing the landscape for accounting and auditing services providers.